RASIONALITAS PEDAGANG PASAR KAGET (STUDI PEDAGANG SAYUR DI PASAR KAGET KARTIKA SARI KECAMATAN RUMBAI) - Sri "; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Pasar surprised Kartika Sari in Rumbai subdistrict. The purpose of this research is to know the rationality of vegetable traders in the market shocked Kartika Sari district Rumbai. The focus topic of this research is the trader's strategy to gain profit. The authors use qualitative methods and use purposive sampling techniques. Data instruments are observations, interviews, polls and documentation. The research finds that the rationality of traders selling in the shocked market is how the vegetable trader can survive sales in the market of surprised Kartika Sari at a cheaper price in comparison with the traditional market, and How they can get more profit to fulfill their needs. And in this research, researchers found the answer to the question that the trader who sells in the market surprised Kartika Sari that they can sell their prices at a cheaper price in the surprised market because, the vegetables they sell in the shocked market It is the leftover vegetable or vegetable sortyman they sell from the morning market, than the vegetable wither and just wasted, better they sell it again in the shocked market, and the vegetables they are selling to get more profit . Keywords: Rationality, Market Shocked